Interstitial pneumonitis related to rituximab therapy for Waldenström's macroglobulinemia - Bai, Xueyan (Clin Case Rep, 2015)
Rituximab-combined therapeutic regimens have been recommended for treatment of Waldenström's Macroglobulinemia (WM). We report one WM patient who developed interstitial pneumonitis after rituximab therapy.